Modelagem empírica para quantificação da deformação residual de uma liga Cu-Al-Be-Nb com efeito memória de forma - Dantas, Marcelo Rodrigues Nunes (2020)
Intelligent materials are, increasingly, stimulating a series of research aimed at different áreas o fknowledge, such as medicine and various Field sof engineering. In particular, we have memory alloys that are metallic alloys with the property that, after apparent plastic deformation, they return to a predefined shape through na appropriate ther mo mechanical process. What ever the application, it is necessary to have na understanding of the behavior of the material, so that it is possible to optimize the use of its potential. Consequently, the broad knowledge of the thermomechanical behavior of shape memory alloys (LMF) is necessary to obtain of high thermal hysteresis, which makes it possible to eliminate theneed for cryogenic media in many applications, considering that the high cost of storage and the difficulties presented in relation to the fast recovery of the alloy under low temperatures are bottlenecks pertinent to the use of this alloy in its conventional form. In this way, mathematical models emerge as na effective alternative for describing this thermo mechanical behavior. In the present work, a mathematical model was developed capable of measuring the residual strain for a Cu-Al-Be-Nb alloy as a function of the variables: strain, temperature, strain rate and number of cycles. Additionally, thein fluence of mechanical cycling was evaluated with the application of intermediate cycles until reaching the total deformation. It is observed that the results obtained through the model are presented with good agreement when compared with the experimental data. It was also found that themo delisable to predict the conditions necessary to obtain maximum residual deformation. In addition, it was observed that mechanical cycling with in termediate cycles did not interfere with the amount of residual deformation when compared to that obtained for a single deformation cycle.